Social, Racial, and Economic Disparities Affecting Outcomes of Hypertensive Adolescents - Kanya Singhapakdi; Amelia Haydel; Marla Johnston; Shengping Yang; Tamara Bradford; Dedrick Moulton; Thomas R. Kimball (The Journal of Clinical Hypertension)
ABSTRACT Essential hypertension is one of the most common conditions managed in pediatric cardiology and can result in lasting deleterious effects on the cardiovascular system. Pediatric hypertension is so prevalent in the United States that it is often referred to as a public health challenge. Social determinants of health (SDH) are the cultural, economic, educational, healthcare accessibility, and political influences in the environment in which an individual is born or lives, all of which can affect that individual's overall health. This study investigated the impact of social determinants such as rurality, food insecurity, transportation challenges, minority status, income, and race on cardiovascular outcomes in adolescent patients with essential hypertension. This study utilizes multiple validated tools including those from the United States Census and the United States Department of Agriculture (USDA). Using these tools, the patients were scored on their social vulnerability based on home address. These scores were then compared with their echocardiographic data, focusing on measures of end‐organ damage known to occur in the setting of hypertension, including but not limited to indexed left ventricular (LV) mass. LV mass is an independent risk factor for future adverse cardiovascular events. In this study, more social vulnerability and low income were associated with a greater indexed LV mass (r = 0.18, p = 0.008). African American race was associated with a higher left atrial (LA) volume (p = 0.03). These findings substantiate that adolescents with essential hypertension are not only impacted by biological factors but also a combination of intersecting social constructs. The results of this study provide both a deeper understanding of the challenges these patients face and the opportunity to develop real‐life interventions that can optimize clinical outcomes.